2020
DOI: 10.1111/bjh.17017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of adults with cytomegalovirus‐associated thrombocytopenia: a case series and literature review

Abstract: Cytomegalovirus (CMV) is a ubiquitous virus that infects people worldwide. CMV is known to trigger thrombocytopenia, but this association is probably underdiagnosed since CMV infection in healthy adults is usually either asymptomatic or causes only mild symptoms. A systematic literature review was carried out and yielded 23 publications that reported 25 patients. All haematology centres in Israel were searched for adult immunocompetent patients with CMV-associated thrombocytopenia, and five new cases were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…In the current research, neutrophil counts were statistically lower in nonsurvivors yet remained above 1.5 (x10³/mL). Various etiological factors may induce thrombocytopenia, including certain infections like COVID-19 pneumonia and cytomegalovirus infection or antimicrobial agents like linezolid [22][23][24] . In our cohort of non-survivors, platelet counts and SOFA scores were clinically significantly low and high, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, neutrophil counts were statistically lower in nonsurvivors yet remained above 1.5 (x10³/mL). Various etiological factors may induce thrombocytopenia, including certain infections like COVID-19 pneumonia and cytomegalovirus infection or antimicrobial agents like linezolid [22][23][24] . In our cohort of non-survivors, platelet counts and SOFA scores were clinically significantly low and high, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was a trend of higher TPO levels in patients with aplastic anemia (AA; Marsh et al, 1996), and TPO mimetics were approved by the Food And Drug Administration (FDA) for use as a single agent in severe AA patients refractory to frontline immunosuppressive therapy due to its stimulatory effect on HSCs and early progenitor cells (Pierri & Dufour, 2019). A literature review (Shragai et al, 2020) of studies involving adult immunocompetent patients with HCMV-associated thrombocytopenia concluded that eltrombopag exhibited excellent efficacy with a response rate of 75%, and it needs to be further assessed in large clinical samples as a potential treatment for HCMV-infected patients with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The first theory suggests that HCMV infection results in damage to the hematopoietic microenvironment, leading to reduced growth factor production and mesenchymal stem cell (MSC) renewal. An impaired microenvironment results in cytopenia and contributes to graft failure in patients after HSCT (Kong et al, 2014; Smirnov et al, 2007). The second theory suggests that autoantibodies that are detected in HCMV‐positive patients (Yaari et al, 2010) directly interact with the platelet membrane or mediate the elimination of immune complexes by the monocyte–macrophage system.…”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus can worsen ITP in patients receiving immunosuppressive treatments because these agents will activate the cytomegalovirus and thus worsen the ITP making it more resistant to treatment. 19 , 20 Helicobacter pylori may “cause” ITP, but only in certain places, e.g., Japan and Italy, is searching for it at diagnosis of ITP routine and is its eradication a uniformly effective approach to ITP. 21 …”
Section: Section I a Young Female Patient With Immune Thrombocytopeni...mentioning
confidence: 99%